Characterisation of the current switch mechanism in two-stage wire array Z-pinches - Burdiak,GC; Lebedev,SV; Harvey-Thompson,AJ; Hall,GN; Swadling,GF; Suzuki-Vidal,F; Khoory,E; Bland,SN; Pickworth,L; de,Grouchy P; Skidmore,J; Suttle,L; et al. (Physics of Plasmas, 2015)
In this paper, we describe the operation of a two-stage wire array z-pinch driven by the 1.4 MA,240 ns rise-time Magpie pulsed-power device at Imperial College London. In this setup, an inversewire array acts as a fast current switch, delivering a current pre-pulse into a cylindrical load wirearray, before rapidly switching the majority of the generator current into the load after a100–150 ns dwell time. A detailed analysis of the evolution of the load array during the pre-pulse ispresented. Measurements of the load resistivity and energy deposition suggest significant bulk heatingof the array mass occurs. The 5 kA pre-pulse delivers 0.8 J of energy to the load, leaving itin a mixed, predominantly liquid-vapour state. The main current switch occurs as the inverse arraybegins to explode and plasma expands into the load region. Electrical and imaging diagnostics indicatethat the main current switch may evolve in part as a plasma flow switch, driven by the expansionof a magnetic cavity and plasma bubble along the length of the load array. Analysis ofimplosion trajectories suggests that approximately 1 MA switches into the load in 100 ns, correspondingto a doubling of the generator dI/dt. Potential scaling of the device to higher currentmachines is discussed. V